Perception of Gully Erosion and Conservation Practices in Agulu-Nanka-Oko and Ekwulobia - Ezeobi, Joseph Uche; Tambe, Enohetta Besong; Aso, Chukwuemeka Johnmark; Ezeobi-Akpaidiok, Abigail Adaobi (Journal of Sustainability and Environmental Management, 2025)
Agulu-Nanka-Oko and Ekwulobia gully erosion is one of the largest of the many gullies in Anambra State. The purpose of this study was to identify and describe the perception of gully erosion and conservation practices in the study area. One hundred (100) questionnaires were purposively administered to local people in the four communities to determine the perceived causes, effects and conservation techniques practised. Household selection was carried out using a proximity-based sampling approach around the major gully sites. Data were collected from primary and secondary sources through the review of related documents, field observations, questionnaire surveys, Focus Group Discussions, and formal and informal interviews. Findings show that most local people recognise and have good awareness of the existence, causes, and impacts of soil erosion. Local people perceived that rainfall, flooding, deforestation, bush burning, sand mining, soil type, lack of drainage channels, and angry gods of the land contributed to gully formation and its effects on the environment and their livelihoods. Soil conservation measures adopted by the local people, such as digging sumps in compounds, have the highest practice in Ekwulobia (90%) and the least in Nanka (15%). Other techniques include tree planting, with high indications in Nanka (70%) and Agulu (68%). Forming a drainage channel was very popular in Oko (20%) and Nanka (14%). The differences in technique variation could be attributed to the choices and perceptions of local people in controlling gully erosion. The Chi-square test of independence was used to assess whether there is a significant association between the communities (Agulu, Nanka, Oko, and Ekwulobia) and the perceived effects of gully erosion. The result of Pearson’s Chi-square (χ² = 11.914, df = 21, p = 0.942) shows no statistically significant relationship between the variables. This indicates that respondents across the four communities reported similar effects of gully erosion. This research has recommended that terrace management will reduce the slope length and, consequently, soil loss. There should be consistent consultation, advice and guidance on the practice of soil and water conservation measures.